Response of cardamom (Elettaria cardamomum Maton) seedlings to vesicular arbuscular mycorrhizal fungi - BAGYARAJ, K R SREERAMULU, D J (Journal of Spices and Aromatic Crops, 1998)
The growth response of cardamom (Elettaria cardamomum) seedlings (cv, Malabar) to 13 different vesicular arbuscular mycorrhizal fungi was tested under mat house conditions at Bangalore, India, In general, seedlings inoulated with the fungi grew taller, had more number of leaves and tillers, increased seedling biomass and uptake of nutrients compared to control seedlings, Among the various mycorrhizal fungi tested, seedlings inoculated with Gigaspora margarita and Glomus monosporum exhibited significantly higher growth with increased uptake of nutrients,